Analisis Pengendalian Kualitas Pada Pengolah Minyak Kelapa Sawit Dengan Metode Six Sigma Pada PT Suryabumi Agrolanggeng - Rismantia, Putri; Widya Setiafindar (Lembaga Pengembangan Kinerja Dosen, 2022)
PT SURYABUMI AGROLANGGENG is a company engaged in the plantation and palm oil processing industry. The problem that occurs in the company is the occurrence of defects in CPO oil in the form of defects in the raw material, namely FFB (Fresh Fruit Bunches), where the defects consist of F00, F0, and F5 defects with large defects, namely 28.16% FFB with fraction 0, then there are 12.07% FFB with a fraction of 00, and there are as many as 18.63% FFB with a fraction 5. From the problems and conditions that occur in the company, quality control can be carried out. One of the quality control techniques is using the six sigma method. Six sigma method is a statistical concept that measures a process related to defects at the level of six (Six) sigma. Six sigma focuses on eliminating defects by emphasizing understanding, measuring, and improving processes. In six sigma there are 5 phase cycles namely Define, Measure, Analyze, Improve, and Control Based on the results of data processing, it is known that the most dominant type of defect is Fraction 0 of 47.4%, from analysis using a fishbone diagram there are 4 factors causing defects, namely human, material, machine, and environmental factors. The improvement solutions obtained are conducting training, increasing work motivation with rewards, designing sorting aids using automatic technology, tightening and increasing supervision during harvesting, paying attention to lighting needs, implementing 5 S, monitoring production room temperature regularly, conducting trials. the machine before being used for the production process, replace the old pipe or sludge tank with a new one.